Determinan Terhadap Penerapan Pasien Safety Pada Masa Pandemi Covid-19 - Nuril Sofiantin; Cipto Susilo; Hermin Husaeni; Glendy Ariando Salomon; Rida' Millati (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
The nurse's physical workload can include lifting and moving patients who cannot move independently, performing medical procedures that require physical endurance, and working long hours without adequate rest periods. The study aimed to determine the physical and mental workload of health workers with the application of patient safety during the COVID-19 pandemic. The design of this study is quantitative research with a cross-sectional approach; the number of samples is 36 respondents. The research variable was an independent variable (mental and physical workload) with a dependent variable (patient safety application). The study's results related the relationship of physical workload with the application of patient safety with a value of p = 0.409 and the relationship of mental workload with the application of patient safety with p = 0.069. It can be concluded that there is no relationship between physical workload and the application of patient safety in the inpatient room. There is no relationship between mental workload and the application of patient safety in the inpatient room. Therefore, hospitals need to provide adequate support and resources to help nurses manage their workload effectively and prevent burnout and workload overload that can negatively impact healthcare workers' mental and physical health